PEGAWAI NEGERI DAN REVITALISASI NILAI-NILAI ETIKA DALAM PELAYANAN PUBLIK - Avela Dewi (Jurnal Manajemen Kepegawaian, 2009)
That the fundamental reason why public services must be given is there a public interest that must beaccomplished by the government because the government has its “responsibility”. In giving this service, thegovernment is supposed to be professional in doing this and be able to take a decision precisely. However, inreality, the government doesn’t have guidance or moral and ethical code of conduct. Related to this condition,it is necessary to make revitalizations for the ethical value of public services by all those civil servants in doingall such tasks as the public services.Key words: public services, ethical public services, ethical code of services.